2000
DOI: 10.1046/j.1365-2958.2000.01815.x
|View full text |Cite
|
Sign up to set email alerts
|

The extremely halophilic archaeon Haloferax volcanii has two very different dihydrofolate reductases

Abstract: SummaryThe gene encoding dihydrofolate reductase, hdrA, from the extremely halophilic archaeon Haloferax volcanii was previously isolated from a spontaneous trimethoprim-resistant mutant in a DNA sequence that had undergone amplification. Here, we show that deletion of hdrA did not affect growth in minimal medium and that the strain carrying the deletion remained sensitive to trimethoprim. A spontaneous trimethoprim-resistant colony was isolated in the hdrA deletion strain and found to possess a new DNA amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 44 publications
0
45
0
Order By: Relevance
“…We have shown elsewhere that this strain displays a growth rate comparable to H26 in supplemented medium (Phillips et al 2008). The folE2 gene can therefore be used as a positive auxotrophic selectable marker adding to the few already available (Ortenberg et al 2000, Bitan-Banin et al 2003, Allers et al 2004.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We have shown elsewhere that this strain displays a growth rate comparable to H26 in supplemented medium (Phillips et al 2008). The folE2 gene can therefore be used as a positive auxotrophic selectable marker adding to the few already available (Ortenberg et al 2000, Bitan-Banin et al 2003, Allers et al 2004.…”
Section: Discussionmentioning
confidence: 83%
“…Haloferax volcanii is one of the rare archaea with both active folate and G + pathways (Gupta 1984, Gupta 1986, Ortenberg et al 2000; however, no folE gene has been identified in its genome. Instead, H. volcanii possesses a folE2 gene (HVO_2348) encoding a newly discovered GTP cyclohydrolase enzyme IB that is involved in archaeosine biosynthesis (El Yacoubi et al 2006, Phillips et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…A 685-bp PCR product, comprising the hdrB coding sequence (Ortenberg et al 2000), was inserted at the XbaI-HindIII sites directly downstream of the pyrE2 gene in pGB70 (BitanBanin et al 2003). To generate pTA409, the 1253-bp pyrE2ThdrB operon was inserted at the PsiI site in pBluescript II, and a 948-bp BmgBI-AciI fragment containing the ori-pHV1/4 DNA replication origin of H. volcanii plasmids pHV1 and pHV4 (Norais et al 2007) was inserted at the PciI site.…”
Section: Construction Of Shuttle Vector Pta409mentioning
confidence: 99%
“…H. volcanii is a genetically stable prototroph that has become a model organism for molecular genetic studies of the archaea (6,21,25). The presence in H. volcanii of an efficient transformation system (5), several shuttle vectors (7,10), and selectable markers (8,15) has made a wide variety of molecular genetic studies possible. However, a key tool for genetic analysis, namely, the availability of an efficient gene knockout system, has been lacking.…”
mentioning
confidence: 99%